Nilai Karakter Birrul Walidain dalam Film Gara-gara Warisan Karya Muhadikly Acho dan Relevansinya terhadap Pendidikan Islam - Umami, Reza; Ichsan, Ahmad Shofiyuddin (QuranicEdu: Journal of Islamic Education, 2024)
This research aimed to reveal the value of Birrul Walidain's character in the film "Gara-Gara Pahlawan" by Muhadikly Acho. Not only that, this research also showed its relevance to the world of Islamic education today. This research method used descriptive qualitative with library research type. Data was taken from primary and secondary sources, while the data analysis technique in this research was content analysis technique. The research results showed that there were several values of Birrul Walidain's character in this film, including: guarding his words, maintaining his attitude, being obedient and doing good, and carrying out his parents' will. The relevance in Islamic education today was the emphasis on the importance of family education and always obeying parents, because these two things were one of the core things in reconstructing the three educational centers in Indonesia in the future.